Theraplay in the Work with Child with ASD - D.V. Bogoliubova-Kuznetsova (Moscow State University of Psychology and Education, 2019)
Theraplay is method of parent-child relations therapy, based on the Attachment theory. This is a structured gaming proactive approach in which the therapist organizes the parent-child relations in the way to compensate for the deficits existing in both and thereby contribute to the development of more harmonious attachment relationships. For structure observation and treatment planning, the interaction between a child and an adult evaluated by a professional according to four criteria: structure, involvement, care and challenge. The optimal combination and nature of these measurements in the interaction of the parent and the child should lead to a harmonization of the child's attachment pattern. Theraplay approach can be used in the work with children with increased anxiety, impaired behavior, attention deficit hyperactivity disorder and autism spectrum disorders. The presented case of applying Theraplay in the Center for Curative Pedagogics with a dyad mother and son with an autism spectrum disorder illustrates the method and its results. In the presented case, indicators in the parameters of involvement and care improved significantly, as mother and son began to enter easily into emotional contact with each other; Mom's understanding of her son's emotional needs improved, which allowed them to be satisfied. The parameter of the challenge after therapy has also undergone positive changes: in the performance of complex task the child receives active emotional support from her mother and after completion, she receives vivid praise and recognition of her achievement.